Effects of sleep deprivation on executive functioning, cognitive abilities, metacognitive confidence, and decision making. Issue 2 (29th October 2018) - Aidman, Eugene; Jackson, Simon A.; Kleitman, Sabina
Summary: Performance on many decision‐making tasks is underpinned by metacognitive monitoring, cognitive abilities, and executive functioning. Fatigue‐inducing conditions, such as sleep loss, compromise these factors, leading to decline in decision performance. Using a 40‐hr sleep deprivation protocol, we examined these factors and the resulting decision performance. Thirteen Australian Army male volunteers (aged 20–30 years) were tested at multiple time points on psychomotor vigilance, inhibitory control, task switching, working memory, short‐term memory, fluid intelligence, and decision accuracy and confidence in a medical diagnosis‐making test. Assessment took place in the morning and night over two consecutive days, during which participants were kept awake. Consistent with previous work, cognitive performance declined after a night without sleep. Extending previous findings, self‐regulation and self‐monitoring suffered significantly greater declines immediately after the sleepless night. These results indicate that the known decline in complex decision‐making performance under fatigue‐inducing conditions might be facilitated by metacognitive rather than cognitive mechanisms.